Method validation for determination of mercury in hydrochloric acid - Krongkrod, Jirasa; Sinthusarn, Anucha; Khunhon, Sorada; Sukmak, Aphiya (Bulletin of Applied Sciences, 2022)
Method validation for determination of mercury in hydrochloric acid in the present work is based on Thai Industrial Standard, TISI 217-2556, which is the test for Hydrochloric acid for industrial used, by Flow Injection Mercury Systems (FIMS). Results showed that the linear range was 0.5 - 10 µg/L. The limit of detection was 0.2 µg/L, and the limit of quantitation was 0.5 µg/L. Bias and intermediate precision showed that the percent recovery and relative standard deviation were 85 - 110 % and 1.0 - 3.0 %, respectively. Measurement uncertainty at 95% confidence limit was less than 20%.